Selective Toxicity of Ag/Tio2 Nanoparticles of Waste Water of Industrial Factories on Muscle Mitochondria Isolated from Solendactylus Scallop: Toxicity of Ag/TiO2 of on Solendactylus scallop - Tanbakosazan, Farahnaz; Derakhshi, Pirouz; Abroomand Azar, Parviz; Ashtari, Khadijeh; Naserzadeh, Parvaneh; Seydi, Enayatollah; Pourahmad, Jalal (Iranian Journal of Pharmaceutical Sciences, 2020)
Industrial wastewater is of global concern due to its severe effects on the environment. Compared with municipal wastewater, industrial wastewater generally contains the high concentration of toxic or no biodegradable pollutants. In recently year, scientific showed that scallop could filtration wastewater. Therefore, it was decided to determine the mechanistic toxicity of wastewater contained NPs (Ag and TiO2) towards isolated mitochondria via reliable methods. Isolated muscle scallop mitochondria were obtained by differential ultracentrifugation on before and after exposure to wastewater. Our results showed that two NPs (Ag and TiO2) induced mitochondrial dysfunction via an increase in mitochondrial reactive oxygen species (ROS) generation, lipid peroxidation (LPO) and mitochondrial membrane potential (MMP) collapse. Finally, Ag-NPs and TiO2-NPs have reduced the level of glutathione (GSH) and also induced apoptosis. Our results suggest that wastewater contained NPs -induced toxicity is the result of a disruptive effect on the mitochondrial respiratory chain, increasing the chance of cell death signaling.